Usefulness of Sonication of Cardiovascular Implantable Electronic Devices to Enhance Microbial Detection - Nagpal, Avish (Am J Cardiol, 2015)
The cardiovascular implantable electronic device (CIED) infection rate is rising disproportionately to the rate of device implantation. Identification of microorganisms that cause CIED infections is not always achieved using present laboratory techniques. We conducted a prospective study to determine whether device vortexing-sonication followed by culture of the resulting sonicate fluid would enhance microbial detection compared with traditional swab or pocket tissue cultures. Forty-two subjects with noninfected and 35 with infected CIEDs were prospectively enrolled over 12 months. One swab each from the device pocket and device surface, pocket tissue, and the CIED were collected from each patient. Swabs and tissues were cultured using routine methods. The CIED was processed in Ringer’s solution using vortexing-sonication and the resultant fluid semiquantitatively cultured. Tissue and swab growth was considered significant when colonies grew on ≥2 quadrants of the culture plate and device was considered significant when ≥20 colonies were isolated from 10 ml of sonicate fluid. In noninfected group, 5% of sonicate fluids yielded significant bacterial growth, compared with 5% of tissue cultures (p = 1.00) and 2% of both pocket and device swab cultures (p = 0.317 each). In infected group, significant bacterial growth was observed in 54% of sonicate fluids, significantly greater than the sensitivities of pocket swab (20%, p = 0.001), device swab (9%, p <0.001), or tissue (9%, p <0.001) culture. In conclusion, vortexing-sonication of CIEDs with semiquantitative culture of the resultant sonicate fluid results in a significant increase in the sensitivity of culture results, compared with swab or tissue cultures.